Quantitative diagnostic advantages of three‐dimensional ultrasound volume imaging for fetal posterior fossa anomalies: Preliminary establishment of a prediction model. (5th September 2019) - Sun, Lijuan; Guo, Cuixia; Yao, Ling; Zhang, Tiejuan; Wang, Jingjing; Wang, Li; Liu, Yan; Wang, Keyang; Wang, Longxia; Wu, Qingqing
Abstract: Objectives: To quantitatively assess prenatal diagnostic performance of three‐dimensional ultrasound (3D‐US) for posterior fossa anomalies (PFA) and establish a preliminarily 3D‐US prediction model. Methods: Sixty singleton fetuses suspected of PFA by 2D‐US presented their detailed 3D‐US evaluation. The surface area of vermis (SAV), brainstem‐vermis, and brainstem‐tentorium angles were measured by 3D‐US. The good prognosis was defined as normal neurodevelopmental outcome. MRI and autopsy were the diagnostic reference standard. Results: There was a significant difference between 2D‐US (60.0%, 36/60) and 3D‐US (94.8%, 55/58) for the diagnostic accuracy ( P < .01). Prenatal 3D‐US prediction model was established with observed/expected SAV as the main predictor (area under the curve [AUC]: 0.901; 95% CI, 0.810‐0.992, P < .001). When it was more than 107.5%, the prognosis seemed to be good (sensitivity: 96.4%, specificity: 26.7%), which led to consideration of mega cisterna magna, Blake pouch cyst, or small arachnoid cyst. The prognosis appeared to be poor when it was less than 73% (sensitivity: 71.4%, specificity: 100%), and the diagnosis tended to be a Dandy‐Walker malformation, vermian hypoplasia, and cerebellar hypoplasia. Brainstem–vermis and brainstem–tentorium angles were the secondary indicators (AUC: 0.689 vs 0.761; 95% CI, 0.541‐0.836 vs 0.624‐0.897, P = .014 vs.001). Conclusions: It seems that the exact types of PFA can be effectively diagnosed by quantitative indicators of 3D‐US. Abstract : What is already known about this topic? The diagnosis of the exact types of posterior fossa anomalies (PFA) might be challenging as they may exhibit a similar appearance in two‐dimensional (2D) sonography, usually on the basis of subjective experience, even in expert hands. The midsagittal plane of the normal fetal brain can be obtained clearly by three‐dimensional ultrasound (3D‐US) volume imaging. The inter‐ and intra‐observer agreement proved to be excellent to measure fetal normal vermis using 3D‐US or magnetic resonance imaging (MRI). What does this study add? 3D‐US has the advantages for prenatally differential diagnosis of PFA compared with 2D‐US. Our experience is that the exact types of PFA can be effectively diagnosed by quantitative indicators of 3D‐US.